First record of bugs (Hemiptera: Coreidae and Pentatomidae) attacking pecan tree fruit in Brazil - Boscardin, Jardel; Corrêa Costa, Ervandil; Pedron, Leandra; Do Nascimento Machado, Dayanna; Maus Da Silva, Jéssica (Revista Colombiana de Entomología, 2016)
Leptoglossus stigma, Leptoglossus zonatus (Hemiptera: Coreidae) and Loxa deducta (Hemiptera: Pentatomidae), have been found attacking Carya illinoinensis (Junglandaceae) fruit, in two 10-year-old plantings, located in areas in the city of Paraíso do Sul, Rio Grande do Sul, Brazil. The record was made in March, 2014, concerning the species from genus Leptoglossus and, in March, 2015, Loxa deducta. This represents, therefore, the first record of these Coreidae and Pentatomidae species bugs-feed on pecan tree fruit in the country.